Hubungan Pemenuhan Kebutuhan Spiritual dengan Kualitas Hidup Pasien Kanker - Putria Carolina; Hermanto Hermanto; Karmita Sari Yanra Katimenta (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Patients diagnosed with cancer spend a lot of energy dealing with diagnosis, therapy, and feelings of instability due to possible relapses, death, complications, and financial problems. They often reach the point where they feel that they are very uncertain, very uncertain position, hopeless. Cancer causes loss of hope, affects physical and mental, and results in various disorders such as loneliness, depression, and failure to adapt—the importance of fulfilling the spiritual needs of cancer patients to improve the optimal quality of life. Fulfilling spiritual needs is finding meaning, purpose, the need for hope, belief in life, oneself, and God. Individuals are said to have good spirituality if the individual has full expectations, are optimistic, and think positively. The research design used a cross-sectional approach, the sampling technique was purposive sampling, and the data analysis was tested using the Spearman Rank with a total sample size of 35 respondents. The results obtained by sig. (2-tailed) with a p-value of 0.000 with a degree of significance p ≤ 0.05, which means H1 is accepted. This study shows a relationship between spiritual fulfillment and quality of life for cancer patients. The study results can be used as an intervention in nursing care to improve the quality of nursing services, especially for cancer patients. The better the spiritual needs of cancer patients can be met, the better the quality of life will be about complex matters such as physical health, psychological conditions, level of independence, social relationships, and the individual's relationship with their environment.